Anti-loss practices in the post-harvest phase in a vegetable supply chain - Marangoni, Suzana Márcia [UNESP]; Filho, Téucle Mannarelli [UNESP]; Bustos Mac-Lean, Priscilla Ayleen [UNESP]; Satolo, Eduardo Guilherme [UNESP] (Centro Universitario de Maringa, 2022)
Due to their highly perishable characteristics, vegetables have the highest levels of losses in the post-harvest phase. The 2030 Agenda for Sustainable Development defines SDG 12, which seeks to ensure sustainable production and consumption patterns, and to reduce by half the per capita food waste in the world, in addition to reducing food losses throughout the entire production chain and supplies. Improving the production chain for these products plays an important role in health, food safety and the fight against hunger. In this sense, this study aims to investigate anti-loss practices in the post-harvest phase in a vegetable supply chain in a municipality in the interior of São Paulo, given the importance of family farming in Brazil and the urgency to reduce food losses. The methodology used was qualitative research, with literature and document review, using the single case study method, carried out with a family farmer, and a questionnaire to collect primary data on the subject. Among the results obtained, it was found that the anti-loss actions carried out in the chain come from the main member (producer), who constantly requests greater attention regarding the way in which the products are presented to the consumer, harvesting as close as possible to the time of delivery to the markets, and collaboration with partners regarding the delivery of quantities according to what is absorbed by the market, avoiding losses in cold chambers.
Práticas antiperdas na fase pós-colheita em uma cadeia de abastecimento de hortaliças
Keywords: Anti-loss practices; Family farming; SDG; Supply chain; Vegetable losses